The Effectiveness of Digital-Based Preconception Education in Improving Adolescent Girls’ Reproductive Knowledge - Rezeki, Sri; Lubis, Desi Handayani; Suhartini, Suhartini; Lumbantobing, Pratiwi; Nasution, Herlia Sumardha (Journal of Applied Nursing and Health, 2026)
Background: Adolescent reproductive health literacy is an important determinant of future maternal and neonatal outcomes. However, limited reproductive health knowledge among adolescents remains a major public health concern, particularly in areas with restricted access to reproductive health information. Digital-based preconception education offers a promising strategy to enhance adolescents’ reproductive health knowledge through accessible and engaging learning media. This study aimed to evaluate the effectiveness of digital-based preconception education in improving reproductive health knowledge among adolescent girls. Methods: This study employed pre pre-experiment one-group pretest–posttest design involving 70 adolescent girls aged 15–19 years in Bangun Rejo Village. Respondents were selected using purposive sampling based on inclusion criteria, including smartphone ownership and active social media use. The intervention consisted of structured digital-based preconception education delivered through educational videos for approximately 30–45 minutes. Data were collected using a validated reproductive health knowledge questionnaire administered before and after the intervention. Data analysis was performed using descriptive statistics and the Wilcoxon Signed-Rank Test at α < 0.05. Results: Before the intervention, most respondents had a moderate level of knowledge (67.1%), whereas after the intervention, the majority demonstrated a good level of knowledge (90%). Statistical analysis revealed a significant improvement in reproductive health knowledge following the digital-based preconception education intervention (p < 0.001). Conclusion: Digital-based preconception education is effective in improving reproductive health knowledge among adolescent girls and may serve as an accessible and practical strategy for strengthening adolescent reproductive health promotion.